2013
DOI: 10.1111/1567-1364.12059
|View full text |Cite
|
Sign up to set email alerts
|

Primers for fourteen protein-coding genes and the deep phylogeny of the true yeasts

Abstract: The Saccharomycetales or ‘true yeasts’ consist of more than 800 described species, including many of scientific, medical and commercial importance. Considerable progress has been made in determining the phylogenetic relationships of these species, largely based on rDNA sequences, but many nodes for early-diverging lineages cannot be resolved with rDNA alone. rDNA is also not ideal for delineating recently diverged species. From published full-genome sequence data, we have identified 14 regions of protein-codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The later addition of RPB1 and RPB2 improved the resolution for the Saccharomycetales yeast species [ 15 ]. Recently, Koufopanou et al [ 37 ] reported primer sets for 14 genes to clarify the topology of basal species among the Saccharomycetales. Of our 30 genes, glutamate synthase and adenosyl homocysteinase were used for multiple gene analysis by Koufopanou et al [ 37 ], and CDC19 was selected as a candidate during the first screening stage but was not used in the published analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The later addition of RPB1 and RPB2 improved the resolution for the Saccharomycetales yeast species [ 15 ]. Recently, Koufopanou et al [ 37 ] reported primer sets for 14 genes to clarify the topology of basal species among the Saccharomycetales. Of our 30 genes, glutamate synthase and adenosyl homocysteinase were used for multiple gene analysis by Koufopanou et al [ 37 ], and CDC19 was selected as a candidate during the first screening stage but was not used in the published analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Koufopanou et al [ 37 ] reported primer sets for 14 genes to clarify the topology of basal species among the Saccharomycetales. Of our 30 genes, glutamate synthase and adenosyl homocysteinase were used for multiple gene analysis by Koufopanou et al [ 37 ], and CDC19 was selected as a candidate during the first screening stage but was not used in the published analysis. Gene duplication in the Tor pathway was also reported in some fungi by Shertz et al [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…We deployed a recent multi-locus sequence approach 63 to examine the evolutionary relationships among the species and known populations of the genus Saccharomyces , including the new Australasian population of S. uvarum described here. Complete coding sequences for the fourteen genes were extracted from the available annotations of six Saccharomyces species 51,64 , ( Saccharomyces Genome Database).…”
Section: Methodsmentioning
confidence: 99%